STRATEGI PEMBELAJARAN BERDIFERENSIASI PAI MELALUI RUANG GTK DALAM KURIKULUM MERDEKA - Iwan Setiawan; Ratno, Dedi; Asep Ahmad Arsyul Munir (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2025)
This study aims to improve the effectiveness of Islamic Religious Education (PAI) learning through the implementation of a differentiated learning model that is aligned with the principles of the Merdeka Curriculum. This model allows teachers to customize learning content, processes, and products based on students' readiness, interests, and learning styles. The research was conducted using a qualitative case study approach at SDN 3 Panaragan, using observation, interview, and questionnaire techniques. The results show that teachers can effectively implement differentiated learning with the help of Ruang GTK platform, which provides diagnostic assessment features, visual materials and tiered evaluation. Learning becomes more participatory, responsive and able to improve student learning outcomes both in terms of cognitive and spiritual. Education personnel also play an important role in supporting the technical smoothness of digital learning. Technology integration through Ruang GTK strengthens teachers' role as facilitators and supports inclusive and adaptive learning. Therefore, this model is recommended as an effective learning strategy in implementing Merdeka Curriculum.